EFECTO DE LA SUPLEMENTACIÓN DE UN ACIDIFICANTE MICRO ENCAPSULADO EN LA RACIÓN SOBRE EL COMPORTAMIENTO PRODUCTIVO DE GORRINOS Y MARRANAS - Delgado F., Carlos (2012)
The objective of the present study was to determine the effect of supplementing acidifiers to weaned piglets and sows on productive and health parameters. In the first assaywas used 360 weaned piglets from21 till 42 days of age, randomly distributed into three treatments: a) control group without acidifier, b) supplemented with microencapsulated acidifier, and c) supplemented with powder acidifier. In the second assay, 27 sows were used fromday 93 of gestation till end of lactation (21 days), randomly distributed into two treatments: a) control group without acidifier, and b) supplemented withmicroencapsulated acidifier. In the first assay, none statistical differences were found between treated groups on bodyweight gain fromweaning till 42 days of age (175 g/day), feed intake (357 g/day per animal), feed conversion index (1.03), and diarrhea cases (19.7%). In the second assay, none statistical differences were found between treated groups on feed intake (4.6 kg/day), bodyweight loss in sows (15.0 kg), number of aliveborn piglets per sow(14.5), bodyweight at birth (1.5 kg), bodyweight at weaning (5.1 kg), mortality(9.5%) and diarrhea cases (16.5%) in piglets, and on the interval between weaning and first postpartum oestrus (7.1 days).